Effect of Soil Classification on Seismic Behavior of SMFs considering Soil-Structure Interaction and Near-Field Earthquakes - Shahrokh Shahbazi; Iman Mansouri; Jong Wan Hu; Armin Karami (Shock and Vibration)
Seismic response of a structure is affected by its dynamic properties and soil flexibility does not have an impact on it when the bottom soil of foundation is supposedly frigid, and the soil flexibility is also ignored. Hence, utilizing the results obtained through fixed-base buildings can lead to having an insecure design. Being close to the source of an earthquake production causes the majority of earthquake’s energy to reach the structure as a long-period pulse. Therefore, near-field earthquakes produce many seismic needs so that they force the structure to dissipate output energy by relatively large displacements. Hence, in this paper, the seismic response of 5- and 8-story steel buildings equipped with special moment frames (SMFs) which have been designed based on type-II and III soils (according to the seismic code of Iran-Standard 2800) has been studied. The effects of soil-structure interaction and modeling of the panel zone were considered in all of the two structures. In order to model radiation damping and prevent the reflection of outward propagating dilatational and shear waves back into the model, the vertical and horizontal Lysmer–Kuhlemeyer dashpots as seen in the figures are adopted in the free-field boundary of soil. The selected near- and far-field records were used in the nonlinear time-history analysis, and structure response was compared in both states. The results obtained from the analysis showed that the values for the shear force, displacement, column axial force, and column moment force on type-III soil are greater than the corresponding values on type-II soil; however, it cannot be discussed for drift in general.